Measurement, modeling, and optimization of sound absorption performance of Kenaf fibers for building applications. (August 2020) - Taban, Ebrahim; Soltani, Parham; Berardi, Umberto; Putra, Azma; Mousavi, Seyyed Mohammad; Faridan, Mohammad; Samaei, Seyed Ehsan; Khavanin, Ali
Abstract: The use of natural fibers in the buildings and construction industries as a sustainable and biodegradable product with the aim of noise pollution control has attracted the attention of many researchers. This work aims to study the acoustic behavior of porous absorbers made of natural Kenaf fibers. To this end, samples of sound absorber were fabricated with thicknesses of 10–40 mm at two different bulk densities of 150 and 200 kg/m 3, and their sound absorption coefficient (SAC) was determined by standing wave sound impedance tube at different air gap cavities. A hybrid numerical-mathematical model was also proposed to investigate the acoustic behavior of the samples. To this end, a code was developed to simulate the 3D virtual structure of samples, and flow resistivity was calculated by numerically solving the flow of air in the structures. Tortuosity and two characteristic lengths were obtained using an inverse method programmed in MATLAB®. These parameters were then imported into the Johnson-Champoux-Allard (JCA) model to predict SACs at different frequencies. Afterward, considering the cost and sound absorption average (SAA), samples were optimized using factorial design. Consequently, the acoustic behavior of the optimized acoustic panels was investigated in the reverberation room in terms of reverberation time and random absorption coefficient. Moreover, in order to provide aesthetically and artistically pleasing appearance, the samples were covered with spacer fabrics, and their sound absorption behavior was also studied. The results revealed the promising sound absorption performance of Kenaf fibers. It was found that the SAC at low, mid, and high frequencies increases significantly with increasing the bulk density. The average of SACs for frequencies above 1250 Hz for samples of 40 mm thickness was found to be 0.95, while these values for samples of 30 and 20 mm thickness were respectively 0.85 and 0.7. The introduction of the air gap was found to improve the SAC at low-frequency bands and shift the peak of absorption toward low frequencies. Very good consistency was observed between the predicted and experimental data. The results of the statistical analysis suggested a thickness of 33 mm and a bulk density of 150 kg/m 3 for the optimized panels. The results showed that the mean of SAC increased from 0.68 to 0.72 after covering the optimized panels with spacer fabrics. Highlights: Normal and random acoustic absorption coefficient of the Kenaf fibers were studied. The effects of sample thickness and airgap behind the samples were investigated. A mathematical method for prediction of sound absorption coefficient was proposed. JCA model have a good agreement with the experimental data. The statistical analysis suggested for optimized acoustic panels.